2020
DOI: 10.1007/s10071-020-01394-z
|View full text |Cite
|
Sign up to set email alerts
|

The relationship between monoaminergic gene expression, learning, and optimism in red junglefowl chicks

Abstract: Intra-species cognitive variation is commonly observed, but explanations for why individuals within a species differ in cognition are still understudied and not yet clear. Cognitive processes are likely influenced by genetic differences, with genes in the monoaminergic systems predicted to be important. To explore the potential role of these genes in association with individual variation in cognition, we exposed red junglefowl (Gallus gallus) chicks to behavioural assays measuring variation in learning (discri… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
10
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 12 publications
(11 citation statements)
references
References 87 publications
1
10
0
Order By: Relevance
“…A recent study by Boddington and collaborators suggested that individual differences in biased cognition can be partially explained by variations in brain gene expression [59]. They analyzed the expression of several dopaminergic and serotonergic genes in the prefrontal cortex of red junglefowls and reported that chicks with higher dopamine D 1 receptor expression were more optimistic, while chicks with higher serotonin 5-HT 2A receptor expression tended to be less optimistic.…”
Section: Pessimistic Judgment Biasmentioning
confidence: 99%
“…A recent study by Boddington and collaborators suggested that individual differences in biased cognition can be partially explained by variations in brain gene expression [59]. They analyzed the expression of several dopaminergic and serotonergic genes in the prefrontal cortex of red junglefowls and reported that chicks with higher dopamine D 1 receptor expression were more optimistic, while chicks with higher serotonin 5-HT 2A receptor expression tended to be less optimistic.…”
Section: Pessimistic Judgment Biasmentioning
confidence: 99%
“…All chicks were tested individually, had previously taken part in behavioral studies, and were habituated to human handling and temporary isolation during testing (Boddington et al, 2020;.…”
Section: Experimental Set-upmentioning
confidence: 99%
“…Further, the expression of specific genes appears to be linked to more than one behavioral trait. For example, gene expression of DRD1 and DRD2 is associated with different aspects of behavior in red junglefowl (optimistic behavior: Boddington et al, 2020;impulsive behavior: Ryding et al, 2021). However, the relationship between D1 and D2 receptors and boldness, activity, and exploration is, as far as we find, not yet explored.…”
mentioning
confidence: 99%
“…Red junglefowl naturally form social hierarchies in which high ranking individuals produce more offspring (Collias et al 1994), forage on food which can be patchily distributed and vary in ease of access (e.g., seeds, fruits, and invertebrates, Collias and Collias 1967), and are a prey species in their natural habitat (Evans et al 1993;Schaller 1984Borah et al 2009). This, along with that red junglefowl are increasingly used for behavioral and cognitive studies (e.g., Boddington et al 2020, Rubene and Løvlie 2021, reviewed in Garnham and Løvlie 2018, made them ideal for this study.…”
Section: Introductionmentioning
confidence: 99%